2021
DOI: 10.1245/s10434-021-10508-x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Thiosulfate Reduces Acute Kidney Injury in Patients Undergoing Cytoreductive Surgery Plus Hyperthermic Intraperitoneal Chemotherapy with Cisplatin: A Single-Center Observational Study

Abstract: Background Cytoreductive surgery (CRS) in combination with hyperthermic intraperitoneal chemotherapy (HIPEC) represents a multimodal treatment concept for patients with peritoneal surface malignancies. The use of intraperitoneal cisplatin (CDDP) is associated with a risk of acute kidney injury (AKI). The aim of this study is to evaluate the protective effect of perioperative sodium thiosulfate (STS) administration on kidney function in patients undergoing CRS and CDDP-based HIPEC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Treatment of db/db mice with GKT136901, a NOX1/NOX4 inhibitor, blocked renal NOX4dependent fibrotic signaling after exposure to high glucose [198]. Of note, H 2 S donors, such as sodium thiosulfate, maintain redox homeostasis by ROS scavenging and modifying cysteine residues on key signaling molecules, which exerts renal protection [199,200]. Vitamin E reduced cardiovascular disease and myocardial infarction events in hemodialysis patients [201].…”
Section: Hypoxia As a Therapeutic Target In Ckdmentioning
confidence: 99%
“…Treatment of db/db mice with GKT136901, a NOX1/NOX4 inhibitor, blocked renal NOX4dependent fibrotic signaling after exposure to high glucose [198]. Of note, H 2 S donors, such as sodium thiosulfate, maintain redox homeostasis by ROS scavenging and modifying cysteine residues on key signaling molecules, which exerts renal protection [199,200]. Vitamin E reduced cardiovascular disease and myocardial infarction events in hemodialysis patients [201].…”
Section: Hypoxia As a Therapeutic Target In Ckdmentioning
confidence: 99%
“…In fact, previously published patient cohorts do not consistently provide information on the extent of parietal peritonectomy or CDDP perfusate concentration, which precludes appropriate comparison. However, we do not intend to rule out that the absence of routinely applied nephroprotective agents 38 , 39 or goal-directed fluid management strategies 34 may have additionally contributed to a rather high incidence of CDDP HIPEC-induced AKI in our patient cohort.…”
Section: Discussionmentioning
confidence: 97%
“…Although some trials have shown the nephroprotective effect of ST, they have been largely retrospective or observational in design. 23 , 24 The OVHIPEC-1 study demonstrated improved survival outcomes in advanced stage ovarian cancer patients and included ST prophylaxis in the protocol, and no renal AEs were reported. 1 Baseline creatinine was similar between the ST and nST groups.…”
Section: Discussionmentioning
confidence: 99%